1969
DOI: 10.1203/00006450-196911000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Nephritis: Early Clinical, Functional, and Morphological Studies

Abstract: ExtractThe accumulation of literature on hereditary nephritis with or without nerve deafness attests to the increased awareness of the existence of this syndrome. I t is the purpose of this report to show that there are distinguishing histologic findings in young patients with minimal disease and normal renal function. Eleven patients were studied; 4 were females and 7 were males. Relevant family histories and clinical laboratory findings are shown in table I. I n all patients, hematuria, gross or microscopic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…This ultrastructural lesions seems to be a peculiar hallmark of Alport's syndrome. The characteristic lesions of podocytes that we observed have already been described [1,17].…”
Section: Discussionsupporting
confidence: 65%
“…This ultrastructural lesions seems to be a peculiar hallmark of Alport's syndrome. The characteristic lesions of podocytes that we observed have already been described [1,17].…”
Section: Discussionsupporting
confidence: 65%
“…Patients with a hereditary nephritis, such as Alport's syn drome, usually present with hematuria [5][6][7] and this may even be present at birth [8]. In fact, Gubler et al [2] have reported in their experience that microscopic hematuria, with or without associated proteinuria, is the first indication of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Further reports [6,7] emphasized GBM thickening as the earliest recognizable change in hereditary nephritis. The recognition of these ultrastructural GBM changes as specific to AS followed in 1972 in detailed descriptions by Spear and Slusser [8] and Hinglais et al [9], confirmed a year later by Churg and Sherman [10].…”
Section: Introductionmentioning
confidence: 99%